STRATEGI GURU DALAM MEMBINA KARAKTER JUJUR PESERTA DIDIK KELAS VI SDN 13 KABILA KABUPATEN BONE BOLANGO - Nur Syaidah Sunusi; Lisdawati Muda; Rinaldi Datunsolang (Institut Agma Islam Hamzanwadi NW Lombok TImur, 2025)
Elementary school education is a formal education level that can shape the character of students in the future. The role of parents and educators in shaping character greatly influences the growth and development of a student. This study aims to model teachers in fostering Inhibiting Factors and Supporting Factors of Teacher Strategies in Fostering Honest Character of Class VI Students of SDN 13 Kabila. The type of descriptive qualitative research in this study is grade VI students, the subjects of which are 16 students and several educators at SDN 13 Kabila with a total of students for the 2025-2026 academic year. In learning activities, this school, which has 214 students, is guided by 20 professional teachers. The results of the analysis of school regulations will be imitated by students. Instilling and good habits so that students are accustomed to implementing the rules in the school without any coercion from anyone, and are not only carried out at school but can also be applied by students at home. The implementation of teacher honesty is in line with the theory, which states that teachers must set a good example for their students, both in terms of speech, personality, dress, socializing and behaving honestly.